1998
DOI: 10.1210/jcem.83.3.4656
|View full text |Cite
|
Sign up to set email alerts
|

An Inherited Mutation Associated with Functional Deficiency of the α-Subunit of the Guanine Nucleotide-Binding Protein Gs in Pseudo- and Pseudopseudohypoparathyroidism1

Abstract: Pseudohypoparathyroidism type Ia (PSP) is a disorder characterized by Albright's osteodystrophy, secondary hyperparathyroidism, lowered G s activity, and resistance of the urinary cAMP excretion to exogenous PTH. The patients had raised basal serum levels of TSH and/or excessive TSH response to TRH. Here we have described a 38-bp deletion at the exon 1/intron 1 boundary of one G s ␣ allele in two mothers with pseudo-PSP and in six offsprings with PSP of a kindred with Albright's osteodystrophy. The deletion el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A similar deletion, c.119_139 + 17del, was previously described in another family and it is reported in ClinVar as pathogenic, resulting in a splice junction loss with the predicted formation of an inactive protein with an altered carboxyl-terminus [ 25 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A similar deletion, c.119_139 + 17del, was previously described in another family and it is reported in ClinVar as pathogenic, resulting in a splice junction loss with the predicted formation of an inactive protein with an altered carboxyl-terminus [ 25 ].…”
Section: Discussionmentioning
confidence: 76%
“…These data confirm what was previously reported by Mantovani et al [ 5 ]. Fisher et al [ 25 ] described another series of familial cases with PHP1A characterized by a high incidence of elevated TSH (5 out of 6 cases) and hypocalcaemia (4 out of 6 cases). However, these authors reported insufficient clinical and biochemical information to describe the disease phenotype and therefore insufficient to be compared with the other familial cases analyzed in our literature review.…”
Section: Discussionmentioning
confidence: 99%
“…In progressive osseous heteroplasia, patients can acquire heterotopic bone formation in the skin and subcutis. Progressive osseous heteroplasia pathomechanisms are thought to be related to pseudopseudohypoparathyroidism, which clinically presents as Albright hereditary osteodystrophy 2,12 …”
Section: Discussionmentioning
confidence: 99%
“…Progressive osseous heteroplasia pathomechanisms are thought to be related to pseudopseudohypoparathyroidism, which clinically presents as Albright hereditary osteodystrophy. 2,12 While a definitive molecular basis has yet to be established, the most supported hypothesis is that this condition occurs as the result of immature multipotent mesenchymal cells differentiating into osteoblasts or chondroblasts as a reaction to local injury and under the influence of certain factors such as venous stasis, edema, local trauma, and inflammation. The expression patterns of bone morphogenetic proteins have been studied in their ability to induce bone formation in vivo with varying results.…”
Section: Causes and Associationsmentioning
confidence: 99%
“…In many cases the mutations result in abnormal RNA processing and lack of expression of the mutant allele, i.e. base substitution at a splice junction site; coding frameshift mutations, premature stop codons, and large deletions [12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24]; Weinstein LS, unpublished data]. One specific 4 base pair (bp) deletion within exon 7 of GNAS1 has been identified in affected members from multiple unrelated PHP Ia kindreds [13, 19, 20, 21, 22].…”
Section: Pseudohypoparathyroidismmentioning
confidence: 99%